Tweets Flooded in Bandung 2016 Floods: Connecting Individuals and Organizations to Disaster Information - Anang Dwi Santoso (Faculty of Geography, Universitas Gadjah Mada, 2019)
In a natural disaster, social media has been widely used as one of the primary communication channels to supplement the traditional ones. However, there is a lack of empirical research analyzing this evidence, therefore the purpose of this study is to identify the information shared by Twitter users during the Bandung Flood of 2016 based on period, location, and account ownership. A dataset of 754 tweets was acquired using the NCapture feature in NVivo for content analysis. The study found that social media has significant benefits primarily when sharing information from affected areas to communities outside the region. In more detail, Twitter is used by 28.4%, primarily by those not impacted by the flood, to express good wishes and memorializing. It is because people in the affected area shared firsthand information (23.8%) to them. Then, in addition to citizens, media, NGOs, government, and community leaders who have been found in earlier studies, actors such as civil service organizations (2.9%) and political parties (0.5%) have also participated in disaster relief.